Adhkār and Aḥzāb in Islamic Thought and Practice: Invocation and Devotion in Egypt Thirteenth-Fifteenth Centuries - Ghorab, Mariam (AUC Knowledge Fountain, 2022)
This thesis examines discourses around duʿāʾ in the disciplines of ḥadīth, Islamic Law, and Sufism during the thirteenth to fifteenth century Egypt. I argue that duʿāʾ shaped Muslim daily life and solidified a community of prayer. Invocations generated a discursive tradition and social organization that allows us to document the experience of this praying public. Prayer was at the heart of daily life, and its significance to Muslim devotion made it the subject of commentaries that analysed its language and its embodiment. Works of ḥadīth archived the plethora of duʿāʾ’s material. Its various manifestations warranted a thorough legal investigation in fiqh texts. The practice of duʿāʾ was detailed in the Sufi texts and the lives of Sufi masters. By looking at the conversation that unfolded across all three intellectual traditions, this thesis attempts to explain how people communicated with the Divine.